DESKRIPSI PROFESIONALISME GURU PENGGERAK PEDESAAN DALAM MENYIKAPI KESENJANGAN KONTEKS SOSIAL, EKONOMI DAN GEOGRAFIS DENGAN GURU PENGGERAK PERKOTAAN - Nuri Rizki Setiawan; Achmad Supriyanto (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2024)
Teacher Mobilization Program is a program initiated to empower teachers as agents of change in the world of education. However, the implementation of this program in various regions shows that there is a gap between the implementation of the program in urban and rural schools, this gap is caused by differences in socio-economic and geographical contexts. In responding to this, driving teachers are required to have high professionalism in responding to their respective socio-economic and geographical contexts. The aim of this research is to analyze the professionalism of driving teachers in responding to their respective socio-economic and geographical contexts in terms of running the driving teacher program they are participating in. The approach used in this research is a qualitative approach with types Systematic Literature Review (SLR) and PRISMA method (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). This research uses standard procedures, namely identification, screening, selection of relevant studies, and in-depth analysis of literature examining the implementation of the Teacher Mobilization Program in various regions with different socio-economic and geographical conditions on the results and effectiveness of the program. The research results show that driving teachers in rural areas and urban areas have gaps in social, economic and geographical terms. However, driving teachers in rural areas with a spirit of professionalism are able to professionally adapt to overcome various challenges and obstacles encountered during the implementation of driving teacher education.